2020
DOI: 10.1021/acsanm.9b01951
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotube Network Electrodes for the Detection of Fentanyl Citrate

Abstract: We prepare disposable single-walled carbon nanotube network electrodes for the detection of the potent opioid fentanyl, currently a leading cause for opioid overdose deaths in the USA. We show repeatable dry transfer of single-walled carbon nanotube (SWCNT) networks to produce robust electrodes. This process directly produces highly conductive SWCNT electrodes without the need for any further modifications required for conventional carbon electrodes. The realized electrode showed low background currents combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 57 publications
3
39
0
1
Order By: Relevance
“…For XAS analysis, SWCNT samples were similarly prepared on a highly conductive (<0.005 Ω cm –1 ) boron-doped Si ⟨100⟩ wafer (Sieger Wafer, Germany). The spectra were recorded at the Stanford Synchrotron Radiation Lightsource (SSRL) according to the protocol described in more detail in ref ( 17 ). The X-ray energies used for carbon (C 1s), oxygen (O 1s), and iron (Fe 2p) were from 260 to 350, 520 to 580, and 695 to 735 eV, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For XAS analysis, SWCNT samples were similarly prepared on a highly conductive (<0.005 Ω cm –1 ) boron-doped Si ⟨100⟩ wafer (Sieger Wafer, Germany). The spectra were recorded at the Stanford Synchrotron Radiation Lightsource (SSRL) according to the protocol described in more detail in ref ( 17 ). The X-ray energies used for carbon (C 1s), oxygen (O 1s), and iron (Fe 2p) were from 260 to 350, 520 to 580, and 695 to 735 eV, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…They have also been used to measure opioid concentrations. 12 17 However, only a few studies on electrochemical detection of oxycodone have been published, 12 and to our knowledge, there are currently no reported studies on the electrochemical behavior of oxycodone together with its main metabolites.…”
mentioning
confidence: 99%
“… 33 It has been shown that SWCNT network electrodes have low charging current and enhanced mass transfer, enabling a high signal-to-noise ratio in electrochemical detection. 34 By means of aerosol chemical vapor deposition (CVD), large areas of porous SWCNT electrodes with high conductivity and surface area can be produced. This enables the production of inexpensive disposable SWCNT electrodes on a wide range of substrates including polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics such as large surface area, high electrical conductivity and ability to catalyze redox reactions, [1][2][3][4] make CNTs an attractive material for electrochemical sensors. In fact, we have shown that as-fabricated pristine CNTs are a suitable material for the detection of neurotransmitter dopamine [5,6] and analgesics such as oxycodone, [7] fentanyl, [8] morphine and codeine. [9] The main methods for fabricating CNTs are chemical vapor deposition, electric discharge and laser ablation, where transition metal particles (Co, Fe, Ni) are used for catalyzing the growth of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Furthermore, we have extensively studied the suitability of pristine iron containing single-walled carbon nanotubes (SWCNTs) for the detection of various analgesics. [7][8][9] Despite these studies, at this stage, there are no clear indications regarding the required amount of iron that enhances electrocatalysis towards opioids, and whether the electrocatalytic properties of Fe-SWCNTs be improved with simple oxidative pretreatment.…”
Section: Introductionmentioning
confidence: 99%